Association Between Childhood-Onset Epilepsy and Amyloid Burden 5 Decades Later - Joutsa Juho; Rinne Juha O; Hermann Bruce; Karrasch Mira; Anttinen Anu; Shinnar Shlomo; Sillanpää Matti (AMER MEDICAL ASSOC, 2022)
IMPORTANCE The effect of childhood epilepsy on later-life cognitive and brain health is an unclear and little-explored issue.OBJECTIVE To determine whether adults with a history of childhood-onset epilepsy exhibit increased brain amyloid accumulation, possibly predisposing to accelerated cognitive impairment or even frank cognitive disorders in later life.
DESIGN, SETTING, AND PARTICIPANTS Forty-one adults from a population-based cohort of individuals childhood-onset epilepsy in southwestern Finland, together with 46 matched population-based controls, with underwent amyloid ligand carbon 11-labeled Pittsburgh Compound B (PiB) positron emission tomography after long-term prospective follow-up. The PiB uptake was quantified as a region to cerebellar cortex ratio. Tracer uptake was evaluated visually and analyzed voxel by voxel over the entire brain to investigate the spatial distribution of amyloid deposition. The study was conducted from May 2011 to October 2013; data analysis was performed from January 2014 to October 2016.
MAIN OUTCOMES AND MEASURES Brain amyloid accumulation.RESULTS The 41 individuals with epilepsy were originally enrolled in the Turku Adult Childhood Onset Epilepsy study at the mean (SD) age of 5.1 (4.5) years (range, 0-14 years). After a mean 52.5 (4.0) years of follow-up, the participants were evaluated (26 [63%] were women; the mean [SD] age was 56.0 [4.3] years). Nine individuals with childhood-onset epilepsy (22%) and 3 control participants (7%) had a visually abnormal PiB scan showing high cortical uptake in at least 1 of the evaluated brain regions (P=.04). In semiquantitative analyses, there was a significant interaction effect indicating higher prefrontal cortex uptake in apolipoprotein E (APOE) epsilon 4 allele carriers than in noncarriers in participants (mean [SD], 1.66 [0.41] vs 1.43 [0.15]) compared with controls (1.40 [0.26) vs 1.41 [0.12]) (group x APOE interaction, F= 6.8; P=.01). In addition, there was a significant group effect showing higher tracer uptake in participants compared with controls (group effect, F= 8.0; P=.006).
CONCLUSIONS AND RELEVANCE Adults with childhood-onset epilepsy, particularly APOE e4 carriers, have an increased brain amyloid load at late middle age. Thus, epilepsy is linked with a biomarker that might be related to accelerated brain aging and can be considered a neurobiological predisposition to later-life cognitive disorders.